The criminal exploitation of ambiguity : a multi-level analysis of fraudulent telemarketers - Coffey, Glenn Steven (2003)
During the past century there have been significant changes in the economic and social structure that have resulted in new forms of criminal opportunities. Fraudulent telemarketers are among those that have seized such opportunities to defraud consumers out of billions of dollars annually. The purpose of this dissertation is to determine the decision-making process of criminal telemarketers and the means by which they commit fraud. Data analysis draws from semi-structured interviews with 48 subjects who have been convicted under federal law. First, the organization, management, and accountability structure of criminal telemarketing enterprises are examined. Next, the interaction process between fraudsters and victims is explored from a social-psychological perspective. The subjects' backgrounds and criminal careers and the lure of criminal telemarketing and the lifestyles it affords are then provided. Finally, the thought processes of fraudulent telemarketers are analyzed in the context of denial of crime, techniques of neutralization, and organizational design, before a rational choice perspective is applied. The author concludes that fraudulent telemarketers embrace the cultural goal of capital accumulation, exploit ambiguity in the law, design diffuse accountability structures in their organization to avoid criminal responsibility, and ultimately ascend n to the status of marginalized middle-class persons